The state of the medical care system of the Donetsk region in the first post-war decade according (to the materials of the statistical office) - Volonyts, Vira; Shypik, Natalia (Skhid, 2023)
The article is devoted to highlighting the regional context of the situation in the field of medical care in the first post-war decade. The authors highlight the key problems faced by the medical system after the expulsion of the Nazi occupiers. The specificity of the medical reform of 1947 implementation at the regional level is analyzed. A complex epidemic situation against the background of post-war destruction is characterized. The urgency of the problem lies in the need to ana-lyze the response of the medical system to the challenges faced by society after the end of the war. Consideration of the subject becomes very relevant in the conditions of a large-scale war, which the Russian Federation has unleashed against our country, and which has already led to a significant degree of destruc-tion of medical and social infrastructure facilities. It is necessary to take into ac-count the experience in order to avoid the mistakes made by the Soviet authorities when restoring the medical network and overcoming epidemics accompanying such social cataclysms as war. The novelty of the study is due to the inclusion in the scientific circulation of information arrays from the documents of the regional statistical office, which reflect certain local specifics. It was established that as a result of the war, the main components of the health care system suffered signifi-cant destruction. The attempt to reform it in these difficult conditions led to am-biguous consequences. A positive aspect was the transition from the production principle of medical care to the territorial one. However, the process of combining polyclinics and outpatient clinics with hospitals took place mainly formally, without taking into account personnel and infrastructural capabilities. A characteristic fea-ture was the insufficient level of medical personnel in the region and the lack of medical and diagnostic equipment. The excessive workload of the doctor in the absence of auxiliary means significantly complicated the diagnosis and affected the quality of medical care. The overall high indices of medical care hid a decline in its quality. The practice of locating medical facilities in poorly adapted premises that did not meet the minimum sanitary and hygienic requirements was wide-spread. Difficult social living conditions in a broad context negatively affected the structure of morbidity, threatened epidemics and affected the level of medical measures efficacy